Disordered Eating Behaviors are Associated with Poorer Diet Quality in Adolescents with Type 1 Diabetes - Tse, Julia (2012)
Disordered eating behaviors may pose a risk for poor long-term health outcomes in patients with type 1 diabetes (T1D). This cross-sectional study examined relations of disordered eating behaviors with diet quality, diet-related attitudes, and diabetes management in adolescents with T1D (N=151, 48% female). Participants, recruited July 2008 through February 2009, completed 3-day diet records and survey measures, including the Diabetes Eating Problem Survey (DEPS) and measures of eating-related attitudes. Biomedical data were obtained from medical records. Participants scoring >1 SD above the mean DEPS were classified as at-risk for disordered eating. The Healthy Eating Index-2005 was calculated to assess diet quality. ANCOVA was used to test for differences between risk groups in diet quality, eating attitudes, and diabetes management, controlling for age, sex, and BMI percentile. Youth at-risk for disordered eating were more likely to be overweight/obese (59.1% vs. 40.9% p=0.01). The at-risk group had poorer diet quality (p=0.003), as well as higher intake of total (p=0.01) and saturated (p=0.007) fat than the low-risk group. The at-risk group reported lower self-efficacy (p=0.005), greater barriers (p<0.001), and more negative outcome expectations (p<0.001) for healthful eating, as well as worse dietary satisfaction (p=0.004). The at-risk group had lower diabetes adherence (p<0.01), less frequent blood glucose monitoring (p<0.002), and higher HbA1c (p<0.001). The constellation of excess weight, poorer dietary intake, and poorer diabetes management associated with youth at-risk for disordered eating suggests potential risk of future poor health outcomes. Attention should be given to healthful weight management, especially among overweight youth with T1D.